Territórios da lavoura de arroz e de soja no Rio Grande do Sul: especificidades na produção do espaço agrário regional / TERRITORIES OF FARM OF RICE AND OF SOY IN THE RIO GRANDE DO SUL: specified in the production of the regional agrarian space - Marcelo Cervo Chelotti; Roberto Barboza Castanho (Sociedade & Natureza)
The organization of the space agrarian gaúcho possesses specified associated its partner-spaceformation, where the farming of rice and of soy they are configured seemingly in territories different.Historically the rice is produced in the south half, tends as characteristics the lease of the earth, hightechnological pattern and to be destined to the internal market. While the soy in the north half isproduced in own lands, also with high technological pattern, and destined mainly for the externalmarket. However, in function of the oscillations of the market, associated the drop of the price of therice, the soy has been occupying significant spaces in typical areas of production of rice.